Temporal contrast enhancement of a femtosecond fiber CPA system by filtering of SPM broadened spectra - Buldt, J.; Mueller, M.; Klas, R.; Eidam, T.; Limpert, Jens; Tuennermann, A. (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
We present a novel approach for temporal contrast enhancement of energetic laser pulses by filtered SPM broadened spectra. A measured temporal contrast enhancement by at least 7 orders of magnitude in a simple setup has been achieved. This technique is applicable to a wide range of laser parameters and poses a highly efficient alternative to existing contrast-enhancement methods.
CRIS-Team Scopus Importer:2023-04-20
Keywords: nonlinear effects; pulse compression; pulse-cleaning; self-phase modulation; Ultrafast lasers